If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2x + -4 = 6 Reorder the terms: -4 + 8x + -2x = 6 Combine like terms: 8x + -2x = 6x -4 + 6x = 6 Solving -4 + 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 6 + 4 6x = 6 + 4 Combine like terms: 6 + 4 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| -3+-s= | | 3/5x+8=-2/5x-6 | | (3x+2)(-8x^2+8x-3)=4 | | -2y+4=-2(2y+4) | | 9x-15=8x-5 | | p+5=-52 | | (X^4+2x^2-x+5)/(x^2-x+1) | | x/3+20=6 | | 2(2x-6)+x+7=180 | | s=p/15 | | 2(2x-6)=x+7 | | Y+4x=2 | | -3-95=-8 | | 1/10x7/100 | | F(x)=x^2-12x-45 | | e^2-10e+9=0 | | 2x-6+x+7=90 | | m^2-3m+3=0 | | 2x-6+x+7=180 | | 2/3p=19 | | 204/54 | | 11b-(-3)=-19 | | 6z-5=6z-z | | 5yv-6y+35v-42= | | B=2t | | 4x^5-3x^4+6x^3-3x^2+3x-5=0 | | t=d/100+1/2 | | (7-s)(-3)= | | 3(-5)-5y=9 | | 4a+8=14-6-4a | | 2k^2+8k+9=0 | | 48/204 |